Barbarisms and slang words in the field of transport - Petrėtienė, Angelika; Lovkys, Vladislavas; Paleckas, Vilmantas; Stulgis, Tomas (Transport, 2006)
The paper analyses the barbarisms and slang words used in the field of transport. It deals with the words that are attributed to the colloquial language. The basis of the work is a questionnaire. The students of the Faculty of Transport Engineering of VGTU and people working in the field of transport answered the questionnaire. The respondents were asked the following questions: “Do you use the given words?”, “Do you know the Lithuanian equivalents of the given words?”, “Does a person speaking correctly make a good impression?”. According to the results of the questionnaire, we can conclude that the respondents know the Lithuanian equivalents of the studied words quite well, but when they communicate, they give preference to barbarisms and slang words of the colloquial language. Most probably they are influenced by the environment, in which they communicate, and the traditional usage. If one or another slang word is used temporarily and then forgotten, it doesn‘t break into the native language. But if barbarisms and slang words are used too often, they become a habit, it and is hard to avoid their usage in other social surroundings. First Published Online: 27 Oct 2010